The Performance of Cadre in Non-Communicable Disease Integrated Coaching Center in Medan City 2023 - Mohammad Irfan; Zulfendri Zulfendri; Jasmen Manurung; Kintoko Kintoko; Mido Ester Sitorus (Randwick International of Social Science Journal, 2023)
The aim of this research is to determine the factors that influence the performance of Posbindu Cadres for Non-Communicable Diseases in Medan City in 2023. This type of research is quantitative research with a cross sectional study design. Data analysis used univariate and bivariate analysis with a sample size of 88 respondents. The results of the research show that the variables that are related are income (p=0.016) and cadre motivation (p=0.011) with the performance of cadres at the Integrated Development Post for Non-Communicable Diseases (Posbindu PTM) in Medan City in 2023. The suggestion for this research is that cadres are always more active in increase responsibility in carrying out Posbindu activities so that the existing programs at Posbindu can be achieved and the Puskesmas is expected to increase the motivation and work ability of cadres in carrying out Posbindu activities in order to increase the activity of Posbindu cadres by providing training about Posbindu programs and activities to cadres on an ongoing basis.